Soaking Salt Solution Increases Moisture Content, Ash Content, Starch Content, Decreases Solubility and Swelling Power Of Banggai Yam Flour - Ramadhani - Chaniago; Darni Lamusu; Fitriani Basrin (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study aims to investigate the effect of salt solution (NaCl) soaking on yam, focusing on food safety, organoleptic quality, and changes in chemical composition during the soaking process. Methodology: The method used was a factorial Complete Random Design with the following treatments: P0 = no treatment; P1 = soaking in 10 g/liter salt solution; P2 = soaking in 30 g/liter salt solution; P3 = soaking in 50 g/liter salt solution. Each treatment was repeated three times, resulting in 12 observation units. Results: The results indicated that higher salt solution concentrations led to increased water, ash, and starch content, while the solubility and swelling power of yam flour decreased. Findings: The study found that salt soaking positively affects the preservation and quality of yam by inhibiting pathogenic microorganisms and slowing down tuber rot. The increased concentration of salt solution was directly proportional to the increase in water, ash, and starch content. Novelty: This research provides new insights into the effects of salt soaking on yam, particularly on its chemical composition and potential benefits for food preservation. Originality: The study offers a detailed analysis of how different concentrations of salt solutions affect the quality and chemical properties of yam, contributing to the understanding of its implications for food safety and health. Conclusions: Soaking yams in higher concentrations of salt solution enhances their preservation by increasing water, ash, and starch content, while reducing solubility and swelling power. Paper Type: Empirical Research Paper Keywords: Flour; Salt; Soaking; Yam Banggai